A Service Learning Model for Special Education Teacher Preparation in Secondary Transition Programming. (August 2018) - May, Michael E.; Chitiyo, Jonathan; Goodin, Theresa; Mausey, Angie; Swan-Gravatt, Crystal
The current article describes the evaluation of a service-based learning model as part of a special education course focused on secondary programming for students with disabilities. A total of 42 preservice teachers and 21 high school juniors and seniors with disabilities actively participated in the service learning project at a local high school. Preservice teachers conducted a transition assessment, developed and implemented lesson plans for postsecondary skill development with a high school student, presented their results to local high school personnel, and completed a self-assessment of their level of confidence in transition education for secondary students. Overall, preservice teachers reported confidence in transition planning and in designing and delivering instructional opportunities based on assessment of high school students' transition needs. Moreover, the preservice teachers met the course learning standards by working directly with high school students. Barriers and recommendations for personnel preparation and research are discussed.